Commercialization of Lesbian Identities in Showtime’s The L-word - Ladendorf, Martina (Culture Unbound, 2010)
The article discusses recent developments in media culture through one case study: The L-word, the first television series narratively centered around lesbian and bisexual characters. The business discourse surrounding the series’ production is examined together with the televised text itself and the merchandize connected to The L-word brand. The main research question is why lesbians, a target group previously deemed uninteresting by advertisers and international media conglomerates, have suddenly become demographically desirable. Media producers show increasing interest in the active audience, and encourage fans’ own creativity, for example through social web 2.0 media productions and events, and intermedia storytelling. This is made possible through the televised text’s discursive re-positioning of lesbian identities. The article argues that lesbian identity is a social construction and that it can be seen as an empty or floating signifier, which is filled with new meanings. It also analyzes the immersive online communities and various other merchandize connected to the series as an aspect of thingification, a process were the media is increasingly occupied with things and brands rather than stories and representations. The result is the branded lesbian, or the lesbian brand, which can be seen as an appropriation of lesbian identities.